Optimizing Ion Pathway in Titanium Carbide MXene for Practical High‐Rate Supercapacitor. Issue 4 (13th December 2020) - Tang, Jun; Mathis, Tyler; Zhong, Xiongwei; Xiao, Xu; Wang, Hao; Anayee, Mark; Pan, Feng; Xu, Baomin; Gogotsi, Yury
Abstract: The lengthened ion pathway in restacked 2D materials greatly limits the electrochemical performance of practically dense film electrodes (mass loading >10 mg cm −2 ). Typical strategies such as the insertion of nanomaterials and 3D‐structure design is expected to reduce the volumetric capacitance of Ti3 C2 T x electrodes, diminishing the dominating advantage of Ti3 C2 T x over other electrode materials. Here, a novel, facile, and controllable H2 SO4 oxidation method is developed for alleviating the restacking issue of Ti3 C2 T x film with few electrochemically inactive side‐products such as TiO2 . A hierarchical ion path "highway" in Ti3 C2 T x film is fabricated with porous structure, atomic‐level increased interlayer spacing, and reduced flake size (through probe‐sonication). As a result, ultra‐high rate performance is obtained with high volumetric capacitance. For a ≈1.1 µm thick Ti3 C2 T x film, capacitance retention of 64% is obtained (208 F g −1 /756 F cm −3 ) when the scan rate is increased from 5 to 10, 000 mV s −1 . Even at higher mass loadings exceeding 12 mg cm −2 (48 µm thickness), the rate capability is still comparable to unoptimized Ti3 C2 T x electrodes with low mass loading (1 mg cm −2 ). Consequently, a high areal capacitance of ≈3.2 F cm −2 is achieved for pathway‐optimized thick Ti3 C2 T x film, which is of great significance for practical applications. Abstract : A concentrated H2 SO4 oxidation technique is developed for etching holes on Ti3 C2 T x MXene, which simultaneously removes side products such as TiO2 . Freestanding film electrodes assembled with H2 SO4 ‐etched small flake Ti3 C2 T x nanosheets show an optimized ion pathway with reduced flake size, increased interlayer spacing, and in‐plane pores. Ultrahigh rate performance is obtained even at high mass loadings exceeding 12 mg cm −2 .